Penerapan Hybrid Contract dalam Pebiayaan Cicil Emas - Silvia, Mega; Abdurrahman, Nana Herdiana; Prasetyo, Yoyok (Lembaga Yasin AlSys, 2023)
Islamic banks that are Shariah compliant offer a wide range of financial services to meet local demands. Gold installment financing is a form of financing offered by several Islamic banks. Gold Bullion (bars) can be purchased with installment payments through the Murabahah contract associated with the Rahn contract. The purpose of this study is to study how hybrid contracts can be used to finance gold purchases over time. In this study, using descriptive analysis techniques (descriptive analysis). The authors use this strategy in an effort to provide a transparent explanation given the available research. The purpose of the descriptive method of analysis is to create a description (description) of the event or situation. The study found that the steps involved in providing gold installment financing are as follows: customer application, NAP preparation, financing approval, contract, gold procurement, and collateral deposit. Gold financing can be repaid for two to five years. The general implementation of gold installment financing is governed by the provisions stipulated in SEBI No. 14/16/dpbs of 2012 concerning gold installment financing products and SEOJK No. 36/SEOJK.03/2015 concerning products and activities of Sharia commercial banks and Sharia Commercial Banks and Sharia Commercial Banks. Customers can use gold as collateral to pay a down payment of at least 20%. However, there are costs involved, including the cost of storing and maintaining the guarantee during the installment period, and the guarantee is insured.